Registration of Unregistered Marriages on the Family Card from the Perspective of Soerjono Soekanto's Legal Effectiveness Theory - Jamil, Faishol; Fakhruddin, Fakhruddin; Izzuddin, Ahmad (Universitas Islam Lamongan, 2023)
AbstractThis study will discuss the registration of unregistered marriages on the Family Card from the perspective of Soerjono Soekanto's legal effectiveness theory. The purpose of this study is to find out what is the legal basis for registering unregistered marriages on a family card? And how is the registration of unregistered marriages on the Family Card from the perspective of Soerjono Soekanto's theory of legal effectiveness? This research uses normative juridical research. Meanwhile, in terms of approach, the authors use the statute approach and conceptual approach. The result of this research is that the registration of unregistered marriages on the Family Card is based on Permendagri No. 108 of 2019 and Permendagri No. 109 of 2019. Meanwhile, the perspective of Soerjono Soekanto's legal effectiveness theory, in terms of legal principles, has a good goal, namely to protect children's rights and accelerate birth certificate ownership. However, the preparation of these legal principles is considered to be less than optimal because it does not meet the principles of drafting legislation so that it overlaps with other laws and regulations. This legal rule also has the potential to produce negative impacts in society, namely the increasingly widespread practice of unregistered marriages.